Evaluasi Pelayanan Asistensi Pelaporan SPT Tahunan Dosen Oleh Relawan Pajak Tax Center AP UIN Sunan Gunung Djati Bandung - Sri Rahayu; Sumyati; Susanti (UIN Sunan Gunung Djati Bandung, 2023)
Every taxpayer, including individual taxpayers, is required to file an annual tax return. However, a lot of taxpayers have issues reporting, thus they require help completing the annual SPT for individual taxpayers. The annual SPT services provided by professors on the campus of UIN Sunan Gunung Djati Bandung are supported by the tax volunteer program run by the AP tax center of that university. Tax Volunteers provide online assistance. This research was conducted using a descriptive method in a qualitative approach. A qualitative approach was carried out by observation, interviews, and document studies to obtain data relevant to the research topic. Determination of informants for interviews using purposive sampling technique. The results of this study indicate that the constraints found included online account problems, from external parties, and also from internal parties